Accounting for competitive advantage: The resource-based view of the firm and the labour theory of value - Bowman, Cliff; Toms, S (Elsevier, 2010)
This article uses accounting concepts to assist the field of strategic management in its search for a theory of value, competitive advantage and superior profitability. Specifically, it argues that the resource-based view of the firm requires a labour theory of value creation. Using the circuit of capital as an organizing framework this article integrates RBV and Marx's value theory, by introducing the notion of value as socially necessary labour time, into the analysis of resource-based advantage. This enables us to identify the impact of particular sources of competitive advantage as they become diffused through an industry. Some resource-based advantages, when eventually imitated lead to an overall reduction in industry profitability, and other advantages lead to increases in industry average profitability.
Keywords: Value creation; Resource-based view; Labour theory of value; Industry profitability